2020
DOI: 10.7554/elife.59442
|View full text |Cite
|
Sign up to set email alerts
|

Collagen-rich omentum is a premetastatic niche for integrin α2-mediated peritoneal metastasis

Abstract: The extracellular matrix (ECM) plays critical roles in tumor progression and metastasis. However, the contribution of ECM proteins to early metastatic onset in the peritoneal cavity remains unexplored. Here, we suggest a new route of metastasis through the interaction of integrin alpha 2 (ITGA2) with collagens enriched in the tumor coinciding with poor outcome in patients with ovarian cancer. Using multiple gene-edited cell lines and patient-derived samples, we demonstrate that ITGA2 triggers cancer cell adhes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 65 publications
(82 reference statements)
1
41
0
2
Order By: Relevance
“…In a corollary fashion, a ten gene signature that includes collagen-remodeling genes regulated by TGFβ1 signaling has been correlated with increased metastasis and poor patient survival [ 218 ]. This is particularly significant as the omentum is collagen rich and serves as a robust site for tumor cell adhesion via integrins [ 219 ].…”
Section: Tgfβ and Emt In The Metastatic Epithelial Ovarian Cancer Envmentioning
confidence: 99%
“…In a corollary fashion, a ten gene signature that includes collagen-remodeling genes regulated by TGFβ1 signaling has been correlated with increased metastasis and poor patient survival [ 218 ]. This is particularly significant as the omentum is collagen rich and serves as a robust site for tumor cell adhesion via integrins [ 219 ].…”
Section: Tgfβ and Emt In The Metastatic Epithelial Ovarian Cancer Envmentioning
confidence: 99%
“…reported that integrin alpha 2 (ITGA2), upregulated in omental metastases of patients with ovarian cancer, can trigger tumor cell adhesion to collagen, and then facilitates the migration and peritoneal metastasis of tumor cells. The speculated mechanism of which is that ITGA2 activates the phosphorylation of focal adhesion kinase and the mitogen-activated protein kinase pathway ( 138 ). In another study, lncRNA CASC9 (cancer susceptibility 9) was revealed to be associated with the prognosis and metastasis of esophageal squamous cell carcinoma (ESCC).…”
Section: Resultsmentioning
confidence: 99%
“…The extracellular matrix (ECM) is a key component of the TME, and undergoes remodeling during many of the stages of metastasis establishment (63)(64)(65). This remodeling plays a key role particularly in the development and progression of many epithelial cancers including ovarian cancer (33,34,(66)(67)(68). Our 10-gene signature, which overlaps with the signature elucidated by Cheon et al, was thus focused on collagen remodeling genes that are implicated in invasion and metastases in cancer (34,67,68).…”
Section: Discussionmentioning
confidence: 98%